Exploring the Reduction in Hospitalization Costs Associated with Next-Day Discharge following Transfemoral Transcatheter Aortic Valve Replacement in the United States. Issue 5 (3rd September 2019) - Lauck, Sandra B.; Baron, Suzanne J.; Sathananthan, Janarthanan; Murdoch, Dale; Webb, John G.; Genereux, Philippe; Kodali, Susheel K.; Reynolds, Matthew; Thompson, Christin; Clancy, Seth; Thourani, Vinod H.; Wood, David A.; et al.
ABSTRACT: Background: Index hospital costs for transcatheter aortic valve replacement (TAVR) remain high. Next-day discharge (NDD) is a safe and feasible strategy in select patients. We sought to explore cost savings associated with NDD TAVR. Methods: We conducted a retrospective observation cohort study of all fee-for-service Medicare beneficiaries who underwent elective, uncomplicated, transfemoral TAVR in 2016. We employed a cross-sectional regression analysis to estimate risk-adjusted hospital costs savings of NDD relative to longer length of stay (LOS), and logistic regression to determine differences in direct home discharge and readmission. Results: Among 14, 765 patients (59.2% of all TAVR), 2, 169 (14.7%) were identified as NDD. They were younger (81.3 vs. 82.2, p < 0.01), more likely to be male (63% vs. 52%, p < 0.01), and had lower Charlson Comorbidity Index scores (2.73 vs. 2.98, p < 0.01). The adjusted cost for NDD was 7, 499 lower compared to non-NDD ( p < 0.001), and 5, 188 when controlling for hospital fixed effects ( p < 0.001); estimated total cost savings ranged from 6, 522, 183 to 16, 265, 331. NDD was associated with higher rates of discharged home (83% vs. 59%, p < 0.0001) without home health (16% vs. 28%, p < 0.0001), and lower incidence of readmission at 30 days [OR 0.72 (0.61–0.86), p = 0.0003], 60 days [0.71 (0.61–0.82), p < 0.0001] and 90 days [0.74 (0.65–0.85), p < 0.0001] than non-NDD. Conclusions: There is significant heterogeneity in LOS after TAVR. Cost savings could be achieved with the implementation of clinical pathways and other strategies. Future research is needed to fully capture the multiple effects associated with LOS.